EP021/#1089 Trends in the incidence of invasive breast cancers in the Republic of China. (4th December 2022) - Liao, Cheng-I; Aryasomayajula, Chinmayi; Johnson, Caitlin; Chan, Chloe; Darcy, Kathleen; Tian, Chunqiao; Kapp, Daniel; Chan, John K
Abstract : Objectives: The aim of this study was to identify trends associated with incidence of breast cancers in Native Chinese from the Republic of China. Methods: Data was obtained from the Taiwan Cancer Registry between 2001 and 2018. SEER*Stat 8.3.9 and Joinpoint regression programs 4.9.0.0 were used to calculate the incidences and trends. The incidence was adjusted by WHO 2000 standard population. Results: From 2001 to 2018, the incidence of breast cancer has increased dramatically from 40.23 to 76.66 (per 100, 000). The highest incidence was in the 60–64 year age group (232.23) and those residing in Taipei City (92.34). The incidence of infiltrating ductal carcinoma was higher at 65.2, while lobular carcinoma was 3.46. The overall incidence of breast cancer has increased over the last 18 years at an average annual percentage change (AAPC) of 3.96% (p<0.001). Of the breast cell carcinoma subtypes, mixed infiltrating ductal and lobular carcinoma had the highest increase of 5.82% (p=0.001), followed by lobular carcinoma (5.54%, p<0.001) and infiltrating ductal (4.08%, p<0.001). In an intersectional analysis, the highest AAPC was seen in younger women (45–49 years) residing in Tainan City with lobular carcinoma at 10.9% (p<0.001). Conclusions: The incidence of invasive breast carcinoma is increasing in Taiwan, especially in younger women (<50 years) in Taipei City. Early screening programs are particularly warranted in these high risk groups. Further studies are warranted to determine potential genetic and social determinant factors associated with this rise in incidence.